Sleep apnoea and hypoventilation in patients with five major types of muscular dystrophy - Min Shi; David M Umbach; Yuanyuan Li; Leping Li; Pallav Halani; Mihye Ahn; Deryck S C Yeung; Bradley Vaughn; Zheng Jane Fan (BMJ Open Respiratory Research)
Background The characteristics of and relationship between sleep apnoea and hypoventilation in patients with muscular dystrophy (MD) remain to be fully understood.Methods We analysed 104 in-laboratory sleep studies of 73 patients with MD with five common types (DMD—Duchenne, Becker MD, CMD—congenital, LGMD—limb-girdle and DM—myotonic dystrophy). We used generalised estimating equations to examine differences among these types for outcomes.Results Patients in all five types had high risk of sleep apnoea with 53 of the 73 patients (73%) meeting the diagnostic criteria in at least one study. Patients with DM had higher risk of sleep apnoea compared with patients with LGMD (OR=5.15, 95% CI 1.47 to 18.0; p=0.003). Forty-three per cent of patients had hypoventilation with observed prevalence higher in CMD (67%), DMD (48%) and DM (44%). Hypoventilation and sleep apnoea were associated in those patients (unadjusted OR=2.75, 95% CI 1.15 to 6.60; p=0.03), but the association weakened after adjustment (OR=2.32, 95% CI 0.92 to 5.81; p=0.08). In-sleep average heart rate was about 10 beats/min higher in patients with CMD and DMD compared with patients with DM (p=0.0006 and p=0.02, respectively, adjusted for multiple testing).Conclusion Sleep-disordered breathing is common in patients with MD but each type has its unique features. Hypoventilation was only weakly associated with sleep apnoea; thus, high clinical suspicion is needed for diagnosing hypoventilation. Identifying the window when respiratory muscle weakness begins to cause hypoventilation is important for patients with MD; it enables early intervention with non-invasive ventilation—a therapy that should both lengthen the expected life of these patients and improve its quality.Cite Now